Basic income with high open innovation dynamics: The way to the entrepreneurial state - JinHyo Joseph Yun; Kyungbae Park; Sung Duck Hahm; Dongwook Kim (Journal of Open Innovation: Technology, Market, and Complexity, 2019)
Currently, the world economy is approaching a near-zero growth rate. Governments should move from a market-failure-oriented to a system-failure-oriented approach to understanding this problem, and transform to an entrepreneurial state to motivate the Schumpeterian dynamics of open innovation. We want to answer the following research question in this study: “How can a government enact policies to conquer the growth limits imposed on the economy by inequality or the control of big businesses?” First, we conducted a literature review to establish the concept of building a causal loop model of basic income with open innovation dynamics. Second, we built a causal loop model which includes basic income and all factors of open innovation dynamics. Third, we proved our causal loop model through a meta-analysis of global cases of basic income. Our research indicates that reflective basic income with permissionless open innovation, capital fluidity, a sharing economy, and a platform tax can motivate open innovation dynamics and arrive at a method by which an entrepreneurial state can conquer the growth limits of capitalism.
Keywords: 650; basic income; capital fluidity; open innovation dynamics; permissionless open innovation; sharing economy